Concrete/Steel Bond in Reinforced Concrete Structures Subjected to Dynamic Loadings: Basis of New Numerical Model - Pierre Rossi (Construction Materials, 2025)
This paper presents a new approach for modeling macrocrack propagation in reinforced concrete structures under both static and dynamic loading conditions. The numerical modeling is based on (1) the use of a probabilistic semi-explicit cracking (PSEC) model for macrocrack propagation and (2) the use of a deterministic damage model for the bond between steel and concrete. Another distinctive feature of the proposed modeling approach is the exclusive use of linear volumetric finite elements, both for macrocrack propagation and for the concrete/steel bond. For the latter, a single layer of volume elements is used along the reinforcement bars. Furthermore, the paper details a methodology for incorporating strain rate effects into the bond model under dynamic loading. It also outlines procedures for identifying the parameters required for both the static and dynamic formulations of the proposed models.